Effect of cyclic loading on the stability of screws placed in the locking plates used to bridge segmental bone defects - Grzeskowiak, Remigiusz M. (J Orthop Res, 2020)
The objective of this study was to evaluate the ex vivo effect of cyclic loading on the stability of screws placed in locking plates used to bridge segmental bone defects. The primary interface stability was assessed using peak reverse torque. Eighteen, 8‐hole stainless‐steel 4.5 mm locking plates and 4.0‐mm self‐tapping locking‐head screws were used to stabilize 40‐mm segmental defects in goat tibiae. Treatment groups included control constructs without cyclic loading (n = 6) and constructs tested to 5000 (n = 6) and 10,000 cycles (n = 6) of 600 N compressive axial loading. The insertion of all screws was standardized to 400 N‐cm insertion torque. Peak reverse torque was measured immediately after screw placement (control), or after the completion of the respective loading cycles. The difference between treatment groups was compared using univariate analysis of variance. The analysis revealed a significant difference in peak reverse torque of the screws among the treatment groups (p = .000). The mean reverse torque values equaled 343.5 ± 18.3 N‐cm for non‐cycled controls, 303.3 ± 25.9 and 296.0 ± 42.9 N‐cm after 5000 and 10,000 cycles, respectively. Among all treatment groups, screws placed in the distal bone segment tended to have lesser peak reverse torque reduction than those placed in the proximal segment and the difference was proportional to the number of cycles (p = .562; p = .255; p = .013 in control, and after 5000 and 10,000 cycles, respectively). Cyclic loading may have a negative effect on the primary stability of screws placed in locking plate constructs used to bridge segmental bone defects and could contribute to the risk of screw loosening.